Still life with shape-shifter - Shinn, Sharon (Shinn, Sharon. Shifting Circle novel., 2012)
"National bestselling author Sharon Shinn presents a passionate, heart-wrenching story of secrets and the lengths we'll go to protect those we love.... Melanie Landon and her half sister share a unique bond. For her entire life, Melanie has hidden the fact that Ann is a shape-shifter. The never-ending deception is a heavy weight to bear, but Melanie is determined to keep Ann's secret and protect her from a world that simply wouldn't understand. For months, Melanie hasn't seen or heard from Ann, in either of her forms. When a man shows up saying he's there about her sister, Melanie fears the worst. But Brody Westerbrook doesn't have information about Ann--he's in search of it. A freelance writer, Brody intends to include Ann in a book he's writing about the existence of shape-shifters. While Melanie is immediately drawn to the stranger on her doorstep, she denies his claims, knowing that trusting him isn't an option. But when Ann finally reappears, looking thin and sick, Melanie realizes exposure is the least of their worries. Protecting her sister has always been an enormous part of Melanie's life, but as Ann's health rapidly deteriorates, Melanie must come to grips with the fact that saving her may mean letting go..."--